Finite element 3D model of a double quantum ring: effects of electric and laser fields on the interband transition - A Radu; C Stan; D Bejan (New Journal of Physics, 2023)
In this work, the changes in the energy of electrons and holes, oscillator strength and interband transition time when external fields are applied to a GaAs/AlGaAs semiconductor double ring grown by the droplet epitaxy technique are theoretically analyzed. We consider a static electric field and an intense laser field nonresonant with the quantum structure, with variable intensities and orientations with respect to the symmetry axis of the quantum ring (QR). In the formalism of the effective mass approximation for electrons and holes, the energies and wavefunctions were numerically computed using the finite element method implemented with an accurate three-dimensional model of the real QR. Laser dressing of the confining potential was performed using the exact integration formula at each point. Our results show major differences between the effects of the two types of applied fields, caused mainly by the static electric-field-induced strong polarizability of the confined electron-hole pair. In addition, the effects of both fields exhibit strong anisotropy in the electronic properties as a result of the particular flattened geometry of the QR. Proper combinations of field strengths and orientations are helpful in designing accurate tools for the sensitive manipulation of interband radiative properties.